ANALISIS SURVEI KEPUASAN PELANGGAN TERHADAP E-COMMERCE DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Eni Pudjiarti; Muhamad Tabrani (STEKOM PRESS, 2021)
Online shopping is the process of purchasing goods / services by consumers to realtime sellers, without services, and through the internet. The development of online business in Indonesia is now very rapid, one of them by shopping online. Online stores or we often call e-commerce is a form of change that is presented by the internet in terms of innovation in shopping by providing various facilities in the transaction process. The aim of the writer is to determine the best e-commerce, therefore the author uses the SAW (Simple Additive Weighting) method because the method is able to make a more precise assessment because it is based on the value of criteria and preference weights that have been determined, besides that the SAW method also can select the best alternative from a number of alternatives because there is a ranking process after determining the weights for each attribute.